Egotist / Napoleon emperor and conqueror - Heuston Burton Kimberley 1960; Kimberley Burton Heuston (New York : Scholastic, 2010)
An engaging biography of Napoleon Bonaparte--one of the most brilliant and reckless generals in history--who declared himself emperor of France in 1804, conquered lands from Portugal to Poland, made kings and queens of his family members, and nearly brought all of Europe to its knees.
U
990